Autobiographical Therapeutic Performance as a Means of Improving Executive Functioning in Traumatized Adults - Ray, Paula; Pendzik, Susana (Frontiers in Psychology, 2021)
This article describes the pilot project Shadows & Light Within: Untold Stories – a two-phase, multi-partner community-based project that explores the hypothesis that Autobiographical Therapeutic Performance can help traumatized individuals to improve executive functioning. A group of 10 individuals (n=10), ranging in age from 32 to 69, with lived experiences at the intersection of trauma, mental health and the court system, were paired with theater mentor-coaches for a 10-month creative group process, in which they shaped their stories into autobiographical performance pieces, through movement, improvisation, story-telling, and self-discovery. In the second phase of the project, their stories were merged into a theater production, weaving movement, song and voice, and performed by an ensemble of experienced actors from the community. Pre and post interviews and self-report standardized measures of executive functioning were used to assist in establishing criteria and direction for future research. The results suggest that the individuals involved in this pilot may have improved executive functioning and acquired more ability to engage in human service programs designed to increase job readiness and enhance adaptive living skills.